"Stay - we will serve you plov!". Puzzles and pitfalls of water research in rural Uzbekistan - Lisa Oberkircher (University of Bonn, Center for Development Research (ZEF), 2011)
This article reflects on the methodology I used to conduct research on water use in rural Uzbekistan. It talks about ethical considerations, data puzzles, interdisciplinarity, and intercultural struggles. About why I will never eat plov again for the rest of my life and why fancy blue licence plates are not all good. Most importantly, it explains which thoughts went into the way I collected and analysed data, how my results have to be read, and how I tried to overcome methodological difficulties of doing research in a remote, traditional, and politically sensitive context such as the province Khorezm of Uzbekistan.
Keywords: 330; Central Asia; field research; hospitality; methodology; political correctness; political sensitivity; research ethics; subjectivity